PENGARUH CELEBRITY ENDORSER, INOVASI PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN AYAM GEPREK BENSU (Studi Pada Mahasiswa Rusunawa II Universitas Islam Malang ) - Muflikhul Ulayanis Arliska; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen)
ABSTRACTThe conduct of this research is to prove the influence of the influence of celebrity endorser, product innovation, and price on consumer decisions to buy a product that has been offered. The research method used is based on the exposure of the above experts related population, then the population that will be used in this study are student in Rusunawa II Universitas Islam Malang using accidental sampling technique obtained by a sample of 62 respondents. The testing technique used is the validity test, reliability test, normality test, multiple linear regression analysis, classic assumption test, and hypothesis test.The results of this study indicate that: 1. Celebrity endorser, product innovation, prices are partially positive and significantly influence consumer purchasing decisions, 2. Celebrity endorsers, product innovation, and Price simultaneously positive prices and significantly influence consumer purchasing decisions Keywords : Celebrity Endorser, Product Innovation, Price